Nutritional management in an elderly man with esophageal and gastric necrosis after caustic soda ingestion: a case report - Rondanelli M; Peroni G; Miccono A; Guerriero F; Guido D; Perna S (Dove Medical Press, 2016)
Mariangela Rondanelli,1 Gabriella Peroni,1 Alessandra Miccono,2 Fabio Guerriero,3 Davide Guido,3,4 Simone Perna1 1Department of Public Health, Neuroscience, Experimental and Forensic Medicine, Endocrinology and Nutrition Unit, University of Pavia, Azienda di Servizi alla Persona di Pavia, Pavia, 2Department of Clinical Sciences, Faculty of Medicine and Surgery, University of Milano-Bicocca, Milan, 3Azienda di Servizi alla Persona di Pavia, 4Department of Public Health, Neuroscience, Experimental and Forensic Medicine, Biostatistics and Clinical Epidemiology Unit, University of Pavia, Pavia, Italy Abstract: The ingestion of corrosive industrial chemical agents, such as caustic soda, that are mostly used for household cleaning, usually occurs accidentally or for suicidal purposes. Multiple protocols are based on documented success in preventing impending complications. In this study, we present a case of a 70-year-old man who swallowed caustic soda in a suicide attempt, causing a development of strong esophageal and gastric necrosis with subsequent gastrectomy and digiunostomy. Initially, the recommended nutritional approach was via percutaneous endoscopic jejunostomy by a polymer and high-caloric formula, with an elevated content of soluble fiber. After 5 months, the medical team removed the percutaneous endoscopic jejunostomy and the patient switched from enteral to oral nutrition. In this step, it was decided to introduce two oral, high-caloric supplements: an energy supplement in powder, based on maltodextrin, immediately soluble in foods or in hot/cold drinks and a high-energy and protein drink, enriched with arginine, vitamin C, zinc, and antioxidants. Oral administration (per os) was well tolerated by consuming homogenized food mixed in water. After 1 month, the patient was discharged from the hospital and was able to eat a regular meal. Keywords: nutritional management, enteral nutrition, gastric necrosis, esophageal necrosis, nutritional supplementation, elderly, caustic soda ingestion